Change in the content of trace elements in the blood of patients with multiple sclerosis depending on the type of course of the disease - Markovska, O. (Journal of Education, Health and Sport, 2017)
The aim was to study the content of trace element in the blood of patients with multiple sclerosis (MS) depending on the type of flow to optimize the diagnostic and prognostic algorithms of the disease. Method of research: the contents of trace element (calcium, magnesium, iron, phosphorus, copper) in the blood serum of 110 patients with MS were determined, which, depending on the type of flow, were divided into three groups. The first group included 12 patients with primary-progredient type of MS course, the second group – 21 patients with secondary-progredient, in the third group – 77 patients with remitting (52 patients in the acute stage and25 in the remission). The control group consisted of 32 healthy people of the corresponding gender and age. Results: It was noted that in general, with MS, and with various types of its course, there is an increase in the blood levels of copper, phosphorus, magnesium and iron reduction. With progredient types of MS, there is a moderate negative correlation between the copper content in the blood and the degree of disability. The increase in the concentration of magnesium in progredient types of MS flow directly depends on the degree of disability and the duration of the disease. An increase in the content of copper, phosphorus and magnesium in the blood, as well as a decrease in the level of iron with a remitting type of MS flow, is observed only in the acute stage, which indicates the pathogenetic and diagnostic significance of these changes and allows using them as additional markers of MS flow activity